Mental Health Impact of COVID-19 on Quarantine Hotel Employees in China - Teng YM; Wu KS; Lin KL; Xu D (Dove Medical Press, 2020)
Yi-Man Teng,1,* Kun-Shan Wu,2,* Kuan-Ling Lin,3 Dan Xu1 1College of Modern Management, Yango University, Fuzhou 350015, People’s Republic of China; 2Department of Business Administration, Tamkang University, Taipei, Taiwan; 3College of Child Development and Education, Yango University, Fuzhou 350015, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kun-Shan Wu Email kunshan@mail.tku.edu.twBackground: The COVID-19 pandemic has had a far-reaching and unprecedented influence on economies worldwide. It has also impacted on the global population’s mental health and caused negative psychosocial effects, which may lead to psychological crises. During the pandemic, the challenges for quarantine hotel employees are not only the increased workloads created by operating a quarantine hotel but also high psychological stress associated with job insecurity, risk of exposure and contagion for themselves, their friends and families. This research attempts to explore COVID-19-related depression, anxiety, and stress among quarantine hotel employees in China. The mental health of quarantine hotel employees, who have faced unprecedented changes, is paramount while they provide hospitality and care for healthcare workers and quarantine guests during mandatory quarantine periods.Methods: This is a cross-sectional study that applied convenience sampling to collect questionnaire samples from 170 quarantine hotel employees in Xiamen, Fujian Province, China, during the COVID-19 pandemic, from May 20 to June 10, 2020. The Depression, Anxiety, and Stress Scale (DASS-21) was used to collect data. The study uses descriptive analysis, chi-square test and binary logistic regression to examine the sociodemographic factors associated with depression, anxiety and stress levels during the COVID-19 pandemic.Results: The results reveal that 43.5% of respondents report moderate to extremely severe symptoms of depression; 68.2% have moderate to extremely severe anxiety symptoms; and 8.2% indicated moderate to extremely severe stress symptoms. Quarantine hotel employees who have a higher level of education are less likely to experience anxiety, and those with higher incomes are less likely to experience depression.Discussion: In order to mitigate the increasing levels of anxiety and depression among their staff, quarantine hoteliers or managers urgently need to implement mental health assistance programs, such as providing extra training in hygiene and knowledge about COVID-19, offering online counseling and psychological support services, training in positive thinking, encouraging staff to keep in touch with their personal support networks, and constructing a resilience model.Keywords: COVID-19, quarantine hotel employee, Depression Anxiety and Stress Scale, DASS-21, mental health